NIMG-59. VALIDATION OF QUANTITATIVE VESSEL SIZE IMAGING (VSI) IN HUMAN GLIOMAS USING IMAGE-GUIDED STEREOTACTIC BIOPSIES. (5th November 2018) - Chakhoyan, Ararat; Leu, Kevin; Harris, Robert; Pope, Whitney; Salamon, Noriko; Yong, William; Lai, Albert; Liau, Linda; Nghiemphu, Phioanh; Cloughesy, Timothy; Ellingson, Benjamin
Abstract: OBJECTIVE: Angiogenesis is critical for brain tumor development and malignant transformation1, influencing both prognosis and response to therapy. The vessel size imaging (VSI) 2 is a quantitative technique that estimates the mean diameter of vessels by using multi-echo spin-and-gradient-echo (SAGE) dynamic susceptibility contrast (DSC) perfusion MRI. In the current study, we compared rCBV and VSI maps to histology-equivalent estimates of vessel density and vessel diameter in high grade glioma patients, using stereotactic image-guided biopsies. METHODS: A total of 26 image-guided biopsies were obtained in 11 glioma patients (7 grade III and 4 glioblastoma). MRI examinations were acquired prior to surgery on a 3T MRI, including multi-echo SAGE DSC perfusion (2x gradient echo, 1x asymmetric echo, and 1x spin-echo). One to three biopsy targets (5mm radius) were defined and stereotactically biopsied. Relative cerebral blood volume (rCBV) was calculated3 using DSC data from a single gradient echo. VSI was quantified as VSIm= 0.867(ADC.rCBV)^(1/2)((R_2^*)/R_2^(3/2)) where ADC is the apparent diffusion coefficient (mm2/s), R2* and R2 are transverse relaxation rates. Histologically estimates of VSIHisto. were obtained as previously modelized.4 Results: Our results suggest that no differences exist in vessel density and VSI from histology between grade III and IV. Indeed, ADC, rCBV and VSI are similar within targets for those grades. We observed a significant correlation between rCBV and vessel density (r=0.42, p=0.032) but not between rCBV and VSIHisto.. Interestingly, VSIMRI was independent of vessel density but highly correlated with VSIHisto. CONCLUSION: MR measures of VSI exhibit a strong relationship to histological measures of vessel diameter in high grade glioma and that independently of blood volume and vessel density. References: 1 Digernes et al. JCBFM 2017. DOI: 10.1177/0271678X17694187 2 Kiselev et al. MRM 2005. DOI: 10.1002/mrm.20383 3 Leu et al. JMRI 2016. DOI: 10.1002/jmri.25227 4 Tropres et al. MRI 2004 DOI: 10.1002/mrm.20017